(untitled) (Sains Humanika, 2017)
Active transport is vital to ensure urban living in a clean, healthy and quality environment. Today, rapid motorisation in Malaysia has been associated with congestion and accidents. Besides, carbon gas emission is polluted the environment and grossly affect people’s quality of life. This study is aimed to predict the variable that effect shift to active transport for short trips. The study employed a survey method, where a set of questionnaire was distributed to 400 samples involved population of five sub-districts in Kota Bharu, which is within 12 km radius from the city centre. The data indicated that almost 100% of the respondents and their households use motorised for daily activities. In addition, 52% of respondents agreed to switch to active transport and 48% the rest did not agree. Willingness to shift to active transport based on state preference survey is significantly influence by level of education and occupation. A study using logistic regression has shown that the highest level of education and occupation of an increasingly less likely a user is to use active transportation. The findings of this study can help relevant agencies such as transportation planners and urban planners to introduce the use of active transport as a mode of transport in city centre.